A Pragmatic Approach for Reproducible Research With Sensitive Data. Issue 4 (2nd August 2017) - Shepherd, Bryan E.; Blevins Peratikos, Meridith; Rebeiro, Peter F.; Duda, Stephany N.; McGowan, Catherine C.
Abstract: Reproducible research is important for assessing the integrity of findings and disseminating methods, but it requires making original study data sets publicly available. This requirement is difficult to meet in settings with sensitive data, which can mean that resulting studies are not reproducible. For studies in which data cannot be shared, we propose a pragmatic approach to make research quasi-reproducible. On a publicly available website without restriction, researchers should post 1) analysis code used in the published study, 2) simulated data, and 3) results obtained by applying the analysis code used in the published study to the simulated data. Although it is not a perfect solution, such an approach makes analyses transparent for critical evaluation and dissemination and is therefore a significant improvement over current practice.